Love and Crime by Ayat Mohammed - Fadhil, Ayat Mohammed (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
A thriller talks about love, regret, friendship, freedom, injustice authority and sacrifice in a world full of darkness and gruesome actions. Tristan is a man who as his name stands for sorrow, is sitting in a room writing to his beloved, Darla, about the debris from the past and the injustice incident that happened to him, also, expressed his concern about her health because Darla was diagnosed with kidney failure, in addition to telling her the reason why he is away and not being with her.